Acral congenital superficial dermal lymphatic malformations in two unrelated cats: clinicopathological, dermoscopic and ultrastructural findings. Issue 4 (6th April 2020) - Legnani, Sara; Abramo, Francesca; Zanna, Giordana; Graziano, Lisa; Cornegliani, Luisa; Roccabianca, Paola
Abstract : Background: Cutaneous vascular malformations (CVM) represent a spectrum of human diseases identified at birth or in paediatric patients and classified according to the type of vessel affected. Confusing classification in human medicine has led to misdiagnoses and frequent nomenclature revision. Cutaneous lymphatic malformations (CLM) are reported sporadically in humans. Objective: To describe the clinicopathological findings of superficial dermal cutaneous lymphatic malformations (SDCLM) in two cats. Animals: Two unrelated adult domestic short hair cats. Methods: The two cats were evaluated clinically and with a dermoscope for recurrent swelling and presence of vesicles oozing serosanguineous fluid affecting the right and left hind foot, respectively, since birth. Skin biopsy specimens were collected for histopathological and immunohistochemical evaluation and electron microscopy. Results: A CVM was suspected based on the age of onset, clinical signs, results of diagnostic imaging and histopathological findings. Dermoscopy was used to describe the alterations of the skin surface. The involvement of the lymphatic vessels was confirmed using immunohistochemical findings and electron microscopy. Conclusion and clinical importance: To the best of the authors' knowledge, this is the first description of the clinical, dermoscopic, histopathological and ultrastructural characteristics of SDCLM in cats resembling the human counterpart. SDCLMs are rare conditions and appropriate histopathological and immunohistochemical confirmation is required to avoid misdiagnosis and mistreatment. Abstract : Background – Cutaneous vascular malformations (CVM) represent a spectrum of human diseases identified at birth or in paediatric patients and classified according to the type of vessel affected. Confusing classification in human medicine has led to misdiagnoses and frequent nomenclature revision. Cutaneous lymphatic malformations (CLM) are reported sporadically in humans. Objective – To describe the clinicopathological findings of superficial dermal cutaneous lymphatic malformations (SDCLM) in two cats. Conclusion and clinical importance – To the best of the authors' knowledge, this is the first description of the clinical, dermoscopic, histopathological and ultrastructural characteristics of SDCLM in cats resembling the human counterpart. SDCLMs are rare conditions and appropriate histopathological and immunohistochemical confirmation is required to avoid misdiagnosis and mistreatment. Résumé: Contexte: Les malformations vasculaires cutanées (CVM) représentent un spectre de maladies humaines identifiées à la naissance ou chez les enfants et sont classés selon le type de vaisseaux atteints. Une classification trouble en médecine humaine a mené à des erreurs de diagnostic et de fréquentes révisions de nomenclature. Les malformations lymphatiques cutanées (CLM) sont rapportées de façon sporadique chez l'homme. Objectifs: Décrire les données clinicopathologiques des malformations lymphatiques cutanées dermiques superficielles (SDCLM) chez deux chats. Sujets: Deux chats européens adultes non apparentés. Méthodes: Les deux chats ont été évalués cliniquement et avec un dermoscope pour écoulement cutané récidivant et la présence de vésicules séro‐sanguinolentes localisées sur les extrémités postérieures respectivement, droite et gauche, depuis la naissance. Des biopsies cutanées ont été prélevées pour histopathologie, immunohistochimie et microscopie électronique. Résultats: Une CVM a été suspectée sur l'âge d'apparition des lésions, les lésions cliniques, les résultats d'imagerie et d'histopathologie. La dermoscopie a été utilisée pour décrire les altérations de la surface cutanée. L'invasion des vaisseaux lymphatiques a été confirmée par immunohistochimie et microcopie électronique. Conclusions et importance clinique: A la connaissance des auteurs, ceci est la première description des caractéristiques cliniques, dermoscopiques, histopathologiques et ultra structuraux de SDCLM chez les chats ressemblants à l'équivalent de l'homme. Les SDCLMs sont des atteintes rares et une confirmation histopathologique et immunohistochimique est nécessaire pour éviter une erreur de diagnostic et un traitement inadapté. Resumen: Introducción: las malformaciones vasculares cutáneas (CVM) representan un espectro de enfermedades humanas identificadas al nacer o en pacientes pediátricos y clasificadas según el tipo de vaso afectado. La clasificación confusa en medicina humana ha llevado a diagnósticos erróneos y una revisión frecuente de la nomenclatura. Las malformaciones linfáticas cutáneas (CLM) se reportan esporádicamente en humanos. Objetivo: describir los hallazgos clinicopatológicos de malformaciones linfáticas cutáneas superficiales (SDCLM) en dos gatos. Animales: dos gatos domésticos adultos de pelo corto no relacionados. Métodos: los dos gatos fueron evaluados clínicamente y con un dermatoscopio debido a la presencia de inflamación recurrente y la formación de vesículas que exudaban líquido serosanguinolento y que afectaban desde el nacimiento a extremidades posteriores derecha e izquierda, respectivamente. Se recogieron muestras de biopsia de piel para evaluación histopatológica e inmunohistoquímica y microscopía electrónica. Resultados: se sospechaba una CVM en función de la edad de inicio y los signos clínicos, los resultados de pruebas de imagen y los hallazgos histopatológicos. La dermatoscopia se utilizó para describir las alteraciones de la superficie de la piel. La afectación de los vasos linfáticos se confirmó mediante hallazgos inmunohistoquímicos y microscopía electrónica. Conclusión e importancia clínica: a entender de los autores, esta es la primera descripción de las características clínicas, dermatoscópicas, histopatológicas y ultraestructurales de SDCLM en gatos que tienen similitud a casos similares en medicina humana. Los SDCLM son condiciones poco frecuentes y se requiere una confirmación histopatológica e inmunohistoquímica adecuada para evitar diagnósticos erróneos y tratamiento inadecuado. Zusammenfassung: Hintergrund: Kutane Blutgefäßmissbildungen (CVM) repräsentieren ein Spektrum an Erkrankungen des Menschen, die bei der Geburt oder bei Pädiatriepatienten identifiziert und nach dem betroffenen Blutgefäßtyp eingeteilt werden. Eine verwirrende Einteilung in der Humanmedizin hat zu falschen Diagnosen und häufiger Revision der Nomenklatur geführt. Beim Menschen werden kutane lymphatische Missbildungen (CLM) sporadisch beschrieben. Ziele: Eine Beschreibung der klinisch‐pathologischen Befunde der oberflächlichen dermalen lymphatischen Malformationen (SDCLM) bei zwei Katzen. Tiere: Zwei nicht verwandte erwachsene europäische Kurzhaarkatzen. Methoden: Die zwei Katzen wurden klinisch sowie mit einem Dermoskop auf wiederkehrende Schwellungen und das Auftreten von Bläschen, die serosanguinöse Flüssigkeit absonderten und seit der Geburt den rechten bzw den linken Hinterfuß betrafen, evaluiert. Die Dermoskopie wurde eingesetzt, um die Veränderungen der Hautoberfläche zu beschreiben. Die Beteiligung von lymphatischen Gefäßen wurde mittels immunhistochemischer Befunde und Elektronenmikroskopie bestätigt. Schlussfolgerung und klinische Bedeutung: Nach bestem Wissen der Autoren handelt es sich hierbei um die erste Beschreibung der klinischen, dermoskopischen, histopathologischen und ultrastrukturellen Charakteristika von SDCLM bei Katzen, welche dem humanen Pendant entspricht. SDCLMs sind seltene Erkrankungen, bei denen eine entsprechende histopathologische und immunhistochemische Bestätigung nötig ist, um eine falsche Diagnose und eine falsche Behandlung zu verhindern. 要約: 背景: 皮膚血管奇形(CVM)は、出生時または小児患者で特定され、罹患血管の種類に応じて分類される人医療領域を示した疾患である。人医学分類がの混乱が誤診を招き、頻繁な命名法の改訂が行われている。人では皮膚リンパ管奇形(CLM)が散発的に報告されている。 目的: 本研究の目的は、2匹の猫における真皮浅層皮膚リンパ奇形(SDCLM)の臨床病理学的所見を説明することであった。 供試動物: 遺伝的に無関係な2匹のドメスティックショートヘア、成猫。 方法: 2匹の猫を臨床的に評価し、出生時からそれぞれ罹患した下右後肢および左後肢の再発性腫脹および滲出性漿液性小水胞の存在についてダーモスコープで評価した。組織病理学的および免疫組織化学的評価および電子顕微鏡検査のため、皮膚生検サンプルを収集した。 結果: 発症年齢、臨床徴候、画像診断の結果および組織病理学的所見に基づいて、CVMが疑われた。皮膚表面の変化を記述するため、ダーモスコピーを使用した。リンパ管の関与は、免疫組織化学的所見および電子顕微鏡を使用して確認された。 結論と臨床的重要性: 著者の知る限りでは、本症例は人に相当する猫のSDCLMの臨床的、皮膚鏡検査、組織病理学的および超微細構造的特徴の最初の記述である。 SDCLMはまれな疾患であり、誤診や誤治療を避けるために適切な組織病理学的および免疫組織化学的確認が必要である。 摘要: 背景: 皮肤血管畸形(CVM)是人类在出生或童年时罹患的一类疾病, 需要根据发病血管的类型进行分类。人医的分类混乱常导致误诊和频繁的命名修订。皮肤淋巴管畸形(CLM)在人医中鲜有报道。 目的: 报告2只猫真皮浅层皮肤淋巴管畸形(SDCLM)的临床病理表现。 动物: 两只不相关的成年家养短毛猫。 方法: 对两只猫进行临床评价, 并在出生后用皮肤镜分别评价是否出现复发性肿胀, 以及右后足和左后足是否存在囊泡渗出浆液血性液体。收集皮肤活检样本, 进行组织病理学和免疫组化评估及电镜观察。 结果: 根据发病年龄、临床体征、诊断性影像学结果和组织病理学结果, 怀疑为CVM。皮肤镜用于描述皮肤表面的变化。免疫组化结果和电镜证实了淋巴管发病。 结论和临床重要性: 据作者所知, 这是首次发现与人类相似的猫SDCLM, 并报告了其临床、皮肤镜、组织病理学和超微结构特征。SDCLM 是罕见疾病, 需要适当的组织病理学和免疫组化证实, 以避免误诊和误治。 Resumo: Contexto: As malformações vasculares cutâneas (CVM) representam um espectro de doenças humanas identificadas ao nascimento ou em pacientes pediátricos e são classificadas de acordo com o tipo de vaso afetado. A classificação confusa em medicina humana levou a diagnósticos errôneos e frequente revisão de nomenclatura. Malformações cutâneas linfáticas (CLM) são relatadas esporadicamente em humanos. Objetivos: Descrever os achados clinicopatológicos de malformações cutâneo linfáticas dérmicas (SDCLM) em dois gatos. Animais: Dois gatos domésticos de pelo curto adultos. Métodos: Os dois gatos foram avaliados clinicamente e com um dermatoscópio por inchaço recorrente e presença de vesículas drenando fluido serossanguinolento afetando a pata direita e esquerda, respectivamente, desde o nascimento. Amostras de biópsia cutânea foram coletadas para avaliação histopatológica e imunohistoquímica e microscopia eletrônica. Resultados: Suspeitou‐se de CVM baseado na idade de surgimento, sinais clínicos, resultados de diagnóstico por imagem e achados histopatológicos. A dermatoscopia foi utilizada para descrever as alterações na superfície da pele. O envolvimento dos vasos linfáticos foi confirmado utilizando os achados de imunohistoquímica e microscopia eletrônica. Conclusão e importância clínica: De acordo com os conhecimentos do autor, esta é a primeira descrição das características clínicas, dermatoscópicas, histopatológicas e ultraestruturais da SDCLM em gatos correlata à forma humana. SDCLMs são doenças raras e a confirmação histopatológica e imunohistoquímica é necessária para evitar erros de diagnóstico e tratamento.